Kontribusi agribisnis manggis terhadap pendapatan rumah tangga petani di Desa Pusparahayu, Kecamatan Puspahiang - Putri S Kamila; Wahid Erawan; Fitri Awaliyah; Tintin Febrianti; Muhammad Nu’man Adinasa (Fakultas Pertanian Universitas Majalengka, 2025)
Mangosteen (Garcinia mangostana L.) is Indonesia's leading tropical horticultural commodity with increasing market demand. West Java, particularly Tasikmalaya Regency, is known as a major production centre. In Tasikmalaya, especially in Pusparahayu Village is a mangosteen producing area with the majority of the harvest for export. This underlines the great opportunity for mangosteen agribusiness to improve farmers' welfare. However, the seasonal nature of the harvest raises questions about the stability of farmers' income to build permanent assets. This phenomenon indicates that the complex management strategy of mangosteen agribusiness beyond harvest needs to be studied in depth. Previous research tends to focus on farm income, without highlighting the important role of post-harvest activities by farmers. This study analysis the socioeconomic characteristics of mangosteen farmers and the contribution of mangosteen agribusiness to farmers' household income in Pusparahayu Village. A descriptive quantitative approach was used through a survey of 30 respondent farmers, selected based on a minimum of 10 years of mangosteen farming experience. Primary data were collected via interviews and observations; secondary data from literature review. Data analysis included calculation of production costs, revenue, profit, and household income from various sources (on-farm, off-farm, non-farm). Results showed that the majority of farmers were over 44 years old (56.67%) with primary school education, mangosteen farming experience averaged 10-20 years. Mangosteen agribusiness contributes dominantly, reaching 97.9% of farmers' total household income, consisting of 33.48% farming and 64.42% post-harvest. Side jobs such as self-employment, trading, or farm labour also support income outside the harvest season.